979 Emphysematous Pyelonephritis in a Diabetic Patient with Horseshoe Kidney: Case Study and Literature Review. (19th August 2022) - Mian, A; Khan, S
Abstract: We present to you the case of a 54-year-old female with a background of horseshoe kidney presenting with a fever, right-sided flank pain, and raised inflammatory markers. This presentation was on a background of recurrent urinary tract infections which were managed conservatively with antibiotics. CT-KUB revealed pockets of gas in both kidneys and within the pelvis, with wall thickening of the left renal pelvis. She subsequently received broad spectrum antibiotics and a suprapubic catheter. Bilateral JJ stents were inserted, and ultrasound was performed in the days following to rule out hydronephrosis. Subsequently, a nephrostomy tube was inserted. The patient clinically improved over time. Horseshoe kidney is a rare anomaly, presenting multiple challenges when managing emphysematous pyelonephritis in these patients. Emphysematous pyelonephritis (EPN) is a necrotising renal infection that leads to the formation of gas in the renal parenchyma, collecting ducts, and surrounding tissue. In the past, multiple eponyms have been used to describe these conditions: 'renal emphysema', 'pneumonephritis'. The pathophysiology of this benign condition is multifactorial. The gas formation that occurs can be either focal or diffuse and has the capability of tracking into perinephric and paranephric spaces. Approximately 90% of these patients have an underlying diagnosis of uncontrolled diabetes mellitus with pathogens that can produce gas, whilst 10% have urinary tract obstructions. EPN is rare, and the occurrence in a diabetic patient with horseshoe kidney has rarely been reported. The presence of a horseshoe kidney makes management more difficult. Few cases have been reported in the literature.